Effect of active mind-body movement therapies on older osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Pi, Congying; Wang, Zixi; Su, Lingyu; Jian, Huaiyu; Liu, Junyan; Zhu, Kun; Zou, Ting; Mao, Xiaoyuan; Zhang, Qinghua; Liu, Zhaoqian (Frontiers in Public Health, 2025)
ObjectiveTo systematically review the literature to quantify and compare the effects of active mind-body movement therapies (AMBMTs) on pain, stiffness, and joint function in older adults with osteoarthritis (OA).MethodsWe searched PubMed, Embase, Cochrane Register of Controlled Trials, Web of Science, ScienceDirect, CINAHL, and PEDro. The outcome measures included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the 36-item Short Form Health Survey (SF-36).ResultsA total of 27 studies involving 1781 patients were obtained. The results of meta-analysis showed that compared with the control group, the patients had significantly lower WOMAC pain score (SMD: −0.50, 95%CI: −0.68, −0.32; p < 0.01), stiffness score (SMD: −0.71, 95%CI: −1.02, −0.40; p < 0.01) and joint function score (SMD: −0.66, 95%CI: −0.85, −0.47; p < 0.01).ConclusionAMBMTs are a complementary therapy to improve pain in older adult patients with OA, of which Tai Ji is the most effective.